The case of a mass death of livestock in the Early Iron Age in the steppe zone of Kazakhstan - Kosintsev P.A.; Beisenov A.Z.; Bachura O.P.; Akhiyarov I.K.; Gimranov D.O., (Вестник археологии, антропологии и этнографии, 2024)
A mass burial of complete and almost complete cattle and small ruminant skeletons found in a pit within the Early Iron Age settlement of Abylai in Central Kazakhstan (49°15'N, 75°07'E) has been studied. The results of archaeological research and archeozoological contexts have shown that the animals’ burial was a single event. The aim of the work was to determine the reasons for the formation of this accumulation. The analysis of skeletal element composition, animal age composition, and the season of their death has been performed. A comparison of species composition, skeletal element composition, age composition, season of animals’ death and taphonomic features between samples from the pit and the cultural layer of the settlement has been made. Significant differences between these samples have been revealed. The animals from the settlement layer were slaughtered during late autumn-winter, while animals from the pit died in early spring. The bones from the pit were almost all intact, while those from the settlement layer had characteristics typical of household waste. Bones from the “layer” have significantly more postmortem modifications than those from the “pit”. The age composition and the skeleton parts ratio between the samples are different. The analysis of the obtained data shows that in the beginning of spring 89 small ruminant and 6 cattle individuals were buried in the pit in a short period of time. According to ethnographic data, this could possibly be interpreted as the burial of animals who died as a result of spring jute. In the steppe zone of Eurasia, jute is the most frequent extreme event leading to mass death of ungulates. Jutes can happen in summer, when grass burns out with drought. But the most large-scale and frequent are winter jutes, when, due to catastrophic snowfalls, grass becomes inaccessible to animals, and spring jutes, when frosts come after a thaw. During jute, many animals die from starvation in a short time. Small ruminants are the most vulnerable because they are the least adapted to breaking ice crusts with their hooves. Cattle are less vulnerable, and even less so are horses. The following archaeological situation has been observed: all animals died in early spring; many of them were buried in a short time; the remains of small ruminants prevail, there are few cattle and no horses; most animals were probably skinned. This picture is most consistent with the burial of animals killed by jute. As an alternative hypothesis, a sacrificial nature of death of the animals has been considered. However, the combination of characteristics of the archaeological and archeozoological contexts of pit filling allows us to reject the latter hypothesis.